Potential Soil Lateral Spreading and Settlement Induced Liquefaction in Indramayu Area - Asrul Sani, Rifki; Soebowo, Eko; Ahmad Sadisun, Imam (Jurnal Teknik, 2025)
An earthquake that had occurred in the Indramayu area in 1847 caused buildings and facilities to collapse, lives were lost, gaps 1-2 feet wide formed in the ground, all buildings in the fort area were severely damaged and could not be rehabited. Based on simulations and evaluations of previous research results in the same area, the source of the damaging earthquake is likely to originate from a shallow earthquake source currently referred to as the Baribis Fault Segment. This study aims to establish a relationship between past earthquake disasters and the potential for their occurrence in the future with the same earthquake source. In this research, we used data from field tests in the form of standard penetration test (SPT) values at 4 technical drilling points, as well as cone penetration test (CPTu) results at 10 test points and CPT results at 13 test points. The three results from the field tests are used in physical and mechanical analysis, as well as safety factors against liquefaction using different PGA value approaches, and the values of these safety factors are considered in estimating potential soil lateral spreading and settlement. The results of the analysis showed that sand sediment layer (fluvial and beach ridges) and sandy sediment layer (delta front silty sand) in the study area had the potential against liquefaction with specific soil settlement and lateral spreading values, depending on PGA values. The highest potential value soil settlement against liquefaction is 0.301 m, while the highest lateral spreading potential of the soil is 0.645 m.